'Buff boys' with brooms: shifting representations of masculinity in Canadian men's curling. Issue 2 (3rd April 2018) - Allain, Kristi A.; Marshall, Barbara
ABSTRACT: This paper explores a shift in masculine sporting identities associated with the sport of curling in Canada. We argue that as curling has become increasingly professionalized, there has been a corresponding shift to representations of male curlers that valourize youth, strength and aggression, in contrast to a previous emphasis on maturity and sportsmanship. After a review of the history and context of curling's popularity as a sport in Canada, we recount these representational shifts, drawing on official documents of curling associations and media coverage of the sport. At the same time, we suggest that extending conventional forms of sporting masculinity to curling sits uneasily beside new initiatives to encourage lifelong participation in sport. We draw on critical masculinity studies and sport studies to argue that age needs to be taken into account when mapping the diversity of masculinities. We further argue that sport is an important context for understanding complex intersections of age and gender, especially as physical activity is increasingly posited as essential to 'successful aging.' We suggest that curling provides an instructive and under-studied example of how these issues conjoin in constructing aging male embodiment, and suggest some directions for further study.